2011
DOI: 10.1099/jmm.0.028910-0
|View full text |Cite
|
Sign up to set email alerts
|

Role of the haem oxygenase/carbon monoxide pathway in Clostridium difficile toxin A-induced enteritis in mice

Abstract: Clostridium difficile is the major cause of antibiotic-associated colitis, a disease with significant morbidity and mortality. This study investigated the role of the haem oxygenase-1 (HO-1)/carbon monoxide (CO) pathway in C. difficile toxin A-induced enteritis in mice. The HO substrate haemin, zinc protoporphyrin IX (ZnPP IX), a specific HO-1 inhibitor, dimanganese decacarbonyl (DMDC), a CO donor, or an equivalent volume of their respective vehicles were injected subcutaneously 30 min prior to local challenge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 43 publications
1
3
0
Order By: Relevance
“…Accordingly, it was previously demonstrated that previous exposure to low concentrations of TcdA (Ͻ10 ng/ml) also induced expression of TGF-␤1 by T84 cells, a human colon adenocarcinoma cell line (24). The present report adds new insight about the intracellular mechanism of activation of the TGF-␤1 pathway in a nontransformed rat small intestinal epithelial cell line with characteristics of crypt epithelial cells and demonstrates that this cytokine is also expressed and produced in response to TcdA in vivo in a well-established TcdA-induced enteritis model in mice (27).…”
Section: Discussionsupporting
confidence: 63%
“…Accordingly, it was previously demonstrated that previous exposure to low concentrations of TcdA (Ͻ10 ng/ml) also induced expression of TGF-␤1 by T84 cells, a human colon adenocarcinoma cell line (24). The present report adds new insight about the intracellular mechanism of activation of the TGF-␤1 pathway in a nontransformed rat small intestinal epithelial cell line with characteristics of crypt epithelial cells and demonstrates that this cytokine is also expressed and produced in response to TcdA in vivo in a well-established TcdA-induced enteritis model in mice (27).…”
Section: Discussionsupporting
confidence: 63%
“…Several bacteria also possess HO enzymes that function to degrade heme that is imported for use as an iron source ( 58 , 59 ). HO activity contributes to pathogenesis in certain bacteria by scavenging iron from heme ( 58 , 60 ).…”
Section: Co Metabolism In Microorganisms: Implications For Pathogenesmentioning
confidence: 99%
“…CO is also implicated in the pathogenesis of Clostridium difficile . Inhibition of host HO activity by administering Zn protoporphyrin IX to mice exacerbated the histopathological alterations elicited by C. difficile toxin A; conversely, pretreatment of mice with a CO donor (dimanganese decacarbonyl) reduced the effect ( 60 ).…”
Section: Heme Oxygenases Of Mammalian Cells: Implications For Infectimentioning
confidence: 99%
“…It is nowadays accepted that CO exerts pleiotropic cellular effects by acting through a number of signaling pathways including those regulated by mitogen-activated protein kinases (MAPKs), peroxisome proliferator-activated receptor gamma (PPAR-γ), cellular ROS production, calcium-dependent potassium channels (Kca) and soluble guanylyl cyclase (sGC) [ 7 , 8 , 9 ]. Moreover, numerous studies have demonstrated that HO-1 and its metabolites, CO and biliverdin can modulate the inflammatory processes [ 10 , 11 ]. CO, acting via MAPKs activity, inhibits the production of pro-inflammatory cytokines (TNF-α, IL-1β) in vitro and in vivo and increases the expression of the anti-inflammatory cytokine IL-10.…”
Section: Introductionmentioning
confidence: 99%